Self-Compassion: The Power of Self- Compassion as a Path to Students Psychological Well-being - Nenny Ika Putri Simarmata; Yurika Natalia Situmorang; Sahala Sitorus; Mustika Gandariang Gulo (Psikostudia : Jurnal Psikologi, 2025)
Students often face various challenges in their academic and social lives, such as academic pressure, uncertainty about the future, and social and economic demands. These challenges can affect students' mental health. During the course of their studies, psychological well-being becomes highly important, as it relates to how satisfied individuals are with their lives, whether they have a clear sense of purpose, and how well they manage stress and emotions. This study aims to examine the effect of self-compassion on psychological well-being among university students in North Sumatra. The research used a quantitative method, with stratified cluster sampling as the sampling technique. The sample consisted of 202 active students from public and private universities across the province of North Sumatra. Data analysis was carried out using simple linear regression with the help of SPSS for Windows 20. The instruments used were the Self-Compassion Scale (SCS) by Neff and Ryff’s Psychological Well-Being Scales (PWB-42). The regression analysis showed a positive and significant effect of self-compassion on psychological well-being (p < 0.05), accounting for 43% of the variance. The level of self-compassion among active university students in North Sumatra was in the moderate category (49%), as was their psychological well-being (60.9%). The findings indicate that the higher the level of self-compassion, the higher the level of psychological well-being among students. This study highlights the importance of developing self-compassion as an effort to enhance students’ psychological well-being. Mahasiswa banyak menghadapi tantangan dalam kehidupan akademik dan sosial, seperti tekanan akademik, ketidakpastian masa depan, dan tuntutan sosial dan ekonomi. Tantangan-tantangan ini dapat mempengaruhi kesehatan mental mahasiswa. Ketika mengikuti proses perkuliahan, kesejahteraan psikologis menjadi sangat penting karena berkaitan dengan seberapa puas seseorang dengan hidupnya, memiliki tujuan yang jelas, dan mampu mengelola stres dan emosi dengan baik. Penelitian ini bertujuan untuk mengetahui pengaruh self-compassion terhadap psychological well-being pada mahasiswa di Sumatera Utara. Penelitian ini menggunakan metode penelitian kuantitatif. Metode pengambilan sampel yang digunakan adalah Stratified Cluster Sampling. Sampel penelitian terdiri dari 202 orang mahasiswa yang merupakan mahasiswa aktif dari PTN dan PTS yang tersebar di provinsi Sumatera Utara. Analisis data menggunakan uji regresi linear sederhana dengan bantuan SPSS for Windows 23. Instrumen yang digunakan adalah Self-Compassion Scale (SCS) oleh neff dan Ryff’s Psychological Well-Being Scales (PWB-42). Hasil analisis regresi menunjukkan bahwa terdapat pengaruh positif dan signifikan self-compassion terhadap psychological well-being (p < 0,05) sebesar 43%. Self-compassion pada mahasiswa aktif Sumatera Utara berada pada kategori sedang (49%). Psychological Well-Being pada mahasiswa aktif Sumatera Utara berada pada kategori sedang (60,9%). Semakin tinggi tingkat self-compassion, maka semakin tinggi pula tingkat psychological well-being mahasiswa. Penelitian ini menunjukkan pentingnya mengembangkan self-compassion dalam upaya meningkatkan kesejahteraan psikologis mahasiswa.